Developing Countries Exports Survival in the OECD: Does Experience Matter? - Céline Carrère; Vanessa Strauss-Kahn (Fondation pour les études et recherches sur le développement international (FERDI), 2014)
This paper focuses on developing countries that export for the first time to the OECD and obtains several important results on export dynamic, linking exports experience and exports survival. Using product level data at the SITC 5 digit level for 114 developing countries on the 1962-2009 period, we show that prior exports experience obtained in non-OCDE markets increases survival in the OECD market. The effect of experience depreciates however rapidly with time: gaining experience for more than two years is worthless. Moreover, a break in export experience prior to entering the OECD reduces the benefit on survival. Geographic export dynamic reveals that experience is acquired in neighbor, easy to access markets before reaching more distant, richer partners and ultimately serving the OECD. Where the experience is acquired does not however matter for survival.
Keywords: C41; F10; F14; O50; 330